Exploring the Experience of Nursing Home Residents Participation in a Hope-Focused Group - Sharon L. Moore; Susan E. Hall; Jennifer Jackson (Hindawi Limited, 2014)
A qualitative intervention was used to explore how older adults living in a long-term care environment (nursing home) understand hope and experience being participants in a group in which a hope intervention was carried out. A group project in which each session focused intentionally on a hope strategy was carried out with a convenience sample of 10 women (ages 75-99) who were members of an existing group. Data were analyzed using thematic analysis of the interviews (conducted before the group intervention was carried out and again at the end), field notes, and collaborative conversations regarding emerging themes. Findings from this study suggest that hope is not static and that it can change over time in response to one's situations and circumstances. Also evident in this study is the potential for using a group process in long-term care to foster hope in an intentional way to make it more visible in the lives of the residents and their environment suggesting that one is "never too old for hope."